Effective psychological therapy for PTSD changes the dynamics of specific large‐scale brain networks. Issue 10 (8th April 2022) - Charquero‐Ballester, Marina; Kleim, Birgit; Vidaurre, Diego; Ruff, Christian; Stark, Eloise; Tuulari, Jetro J.; McManners, Hugh; Bar‐Haim, Yair; Bouquillon, Linda; Moseley, Allison; Williams, Steven C. R.; Woolrich, Mark W.; et al.
Abstract: In posttraumatic stress disorder (PTSD), re‐experiencing of the trauma is a hallmark symptom proposed to emerge from a de‐contextualised trauma memory. Cognitive therapy for PTSD (CT‐PTSD) addresses this de‐contextualisation through different strategies. At the brain level, recent research suggests that the dynamics of specific large‐scale brain networks play an essential role in both the healthy response to a threatening situation and the development of PTSD. However, very little is known about how these dynamics are altered in the disorder and rebalanced after treatment and successful recovery. Using a data‐driven approach and fMRI, we detected recurring large‐scale brain functional states with high temporal precision in a population of healthy trauma‐exposed and PTSD participants before and after successful CT‐PTSD. We estimated the total amount of time that each participant spent on each of the states while being exposed to trauma‐related and neutral pictures. We found that PTSD participants spent less time on two default mode subnetworks involved in different forms of self‐referential processing in contrast to PTSD participants after CT‐PTSD (mtDMN + and dmDMN + ) and healthy trauma‐exposed controls (only mtDMN + ). Furthermore, re‐experiencing severity was related to decreased time spent on the default mode subnetwork involved in contextualised retrieval of autobiographical memories, and increased time spent on the salience and visual networks. Overall, our results support the hypothesis that PTSD involves an imbalance in the dynamics of specific large‐scale brain network states involved in self‐referential processes and threat detection, and suggest that successful CT‐PTSD might rebalance this dynamic aspect of brain function.